Physical properties and dynamics of forest fuels in an oak forest - Martínez Villa, Juan Leyver; Rodríguez-Trejo, Dante Arturo; Borja-de la Rosa, María Amparo; Rodríguez Yam, Gabriel Arcángel (Instituto de Ecología, A.C., 2018)
In this work physical properties relevant in estimations of fire behavior and the forest fuels dynamics in an oak forest in the Estado de Mexico, Mexico were analyzed and evaluated. The evaluation was conducted along the forest fires season. It was estimated: i) the basic density and moisture content of woody fuels by time lag; ii) the forest fuel load in three ways; and iii) the forest fuels dynamics. The basic densities of the woody fuels in the study site followed a decreasing tendency: 1h = 0.585 g cm-3, 10 h = 0.478 g cm-3, and 100 h = 0.412 g cm-3. The woody fuel load estimated with basic densities from the collected material was the lowest: 11.6% less than the value obtained using conifer basic densities, and 43% less than using the basic density of oaks from bibliography. The incorporation rate of fuels was equal to 40.532 Mg ha-1, along the fire season, with 62.9% (25.491 Mg ha-1) for leaf litter, and 18.8% (7.603 Mg ha-1) for woody fuels. The decomposition rate (k) during the fire season was of 0.0827 for leaf litter, and for woody fuels 0.0861 for 1 h time lag, and 0.0404 for 10 h time lag. Biomass load added to the forest floor at the end of the season increased to an  accumulated load of 205% for 1 h and 10 h time lag for branches, while for the leaf litter was 58.7%.